Exogenous Application of Growth Enhancers Mitigate Water Stress in Wheat by Antioxidant Elevation - Nawaz, Hamid; Yasmeen, Azra; Anjum, Muhammad A.; Hussain, Nazim (Frontiers in Plant Science, 2016)
TThe present study was conducted to investigate the response of two wheat cultivars (AARI-11 and Millat-11) to a foliar application of four growth enhancers which include: {H2O (water), MLE30 (moringa leaf extract), KCl (potassium chloride) and BAP (benzyl-amino purine)}, within the six irrigation water-regimes which are applied at the various critical growth stages such as crown root initiation (CRI), tillering (T), booting (B) and heading (H). Irrigation water-regimes include: CRI+T+B, CRI+T, CRI+B, T+B, T+H and control (CRI+T+B+H). The growth enhancers i.e. H2O, MLE30 (1:30), KCl (2%) and BAP (50 mg L-1) were applied @ 500 L ha-1 at tillering and heading stages. The results demonstrated some increased quantities of both enzymatic (superoxide dismutase, peroxidase, catalase) and non-enzymatic (ascorbic acid, phenol) antioxidants in leaves of AARI-11 when MLE30 was applied under T+B and T+H irrigation water-regimes. Similar results were also observed in the case of leaf chlorophyll “a” & “b” and K+ contents in both cultivars under control, T+B and CRI+T+B irrigation water regimes. AARI-11 produced the highest biological and grain yield, due to the application of MLE30 and BAP under control, CRI+T+B, T+B and T+H irrigation water-regimes. However, KCl lagged behind among the treatments set for both cultivars under all the irrigation water-regimes. Foliar spray of MLE30 remained prominent growth enhancer and stresses mitigating agent under water deficit conditions particularly under T+B and T+H irrigation water-regimes. Moreover, economic analysis indicated that the foliar application of MLE30 is a cost effective and environment friendly strategy for the maximum yield and income.